2017
DOI: 10.1021/acs.nanolett.6b04771
|View full text |Cite
|
Sign up to set email alerts
|

Direct Blow-Spinning of Nanofibers on a Window Screen for Highly Efficient PM2.5 Removal

Abstract: Particulate matter (PM) pollution has caused many serious public health issues. Whereas indoor air protection usually relies on expensive and energy-consuming filtering devices, direct PM filtration by window screens has attracted increasing attention. Recently, electrospun polymer nanofiber networks have been developed as transparent filters for highly efficient PM removal; however, it remains challenging to uniformly coat the nanofibers on window screens on a large scale and with low cost. Here, we report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(172 citation statements)
references
References 24 publications
3
169
0
Order By: Relevance
“…The results revealed that the pressure drop of all the samples was less than 25 Pa (Fig. 7), and the lowest pressure drop was 8.4 Pa for sample 11, which was much smaller than the values from other reports [7,18]. The low pressure drop indicated that high air exchange rate could be expected.…”
Section: Pressure Dropmentioning
confidence: 66%
See 1 more Smart Citation
“…The results revealed that the pressure drop of all the samples was less than 25 Pa (Fig. 7), and the lowest pressure drop was 8.4 Pa for sample 11, which was much smaller than the values from other reports [7,18]. The low pressure drop indicated that high air exchange rate could be expected.…”
Section: Pressure Dropmentioning
confidence: 66%
“…superfine and uniform fiber diameter, very large specific surface area, very high porosity, very small and uniform pore size. Khalid had applied Polyacrylonitrile (PAN), Poly (vinyl pyridine) (PVP), Poly (methyl methacrylate) (PMMA), and Nylon-66 nano-fibrous membrane onto metallic mesh and nylon mesh to capture PM2.5 [7]. Their samples had good transparency and very high filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…29 Compared with O1s spectrum of CB, new peak of O1s spectrum located at 532.3 eV (C=O) is detected in GCB, indicating the formation of ester group on its surface ( Figure 3E). 30 The N1s spectrum of GCB is comprised of two peaks of 398.9 (C-N) and 400.8 eV (NH), confirming the formations of amine and amide groups on its surface ( Figure 3F). 31,32 All these results of XPS further confirm the introduction of carbamate groups on CB surface.…”
Section: Surface Chemistry and Morphology Of Carbamate-terminated Cbmentioning
confidence: 72%
“…After grafting, two additional peaks in C1s spectrum at 285.6 and 287.6 eV, respectively corresponding to functional groups of C–N and C=O are observed on the GCB surface (see Figure D) . Compared with O1s spectrum of CB, new peak of O1s spectrum located at 532.3 eV (C=O) is detected in GCB, indicating the formation of ester group on its surface (Figure E) . The N1s spectrum of GCB is comprised of two peaks of 398.9 (C–N) and 400.8 eV (NH), confirming the formations of amine and amide groups on its surface (Figure F) .…”
Section: Resultsmentioning
confidence: 95%
“…Electrospun fibrous membranes possess several fascinating features that make them very attractive for separation and adsorption of contaminants, such as a large surface-to-volume ratio, high porosity, interconnected open pore structure, and high permeability [6][7][8][9]. In particular, porous electrospun nanofibers have been proposed to enhance the performance with higher absorbance capacity and separation efficiency [10].…”
Section: Introductionmentioning
confidence: 99%